Consumer perceptions of cobrands: the role of brand positioning strategies. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – Cobranding is increasingly popular as a strategy for commercial success. Brand positioning strategies are central to marketing, yet the impact of perceptions of parent brands' positioning on consumers' perceptions of cobrand positioning has not been investigated. The aim of the present study is to fill this gap.Design/methodology/approach – Employing a quasi‐experimental design, the authors create cobranding scenarios in three product categories (tablet computers, cosmetics, and smart phones). The data are collected via structured questionnaires resulting in 160 valid responses. The data are analyzed employing Partial Least Squares‐based Structural Equation Modeling (PLS‐SEM), and consumer evaluation of cobrands is tested in relationship to the prior positioning of the parent brands, product fit and brand fit, along with post‐alliance positioning perceptions of the partner brands.Findings – The results confirm brand positioning as a robust indicator of consumer evaluation of cobrands. Positioning perceptions of partner brands are positively related to cobrand positioning perceptions. In addition, pre‐alliance positioning significantly relate to post‐alliance positioning, confirming cobranding as a viable strategy for partner brands.Research limitations/implications – The paper recommends research that could reveal the impact of differential brand equities of partner brands, such as, between a high‐equity brand and a low/moderate‐equity brand, mixed brand alliances – product/service; service/service, and at different levels of partner brand familiarity.Practical implications – Managers should design cobrand positioning based on existing positioning perceptions of the partner brands, rather than focussing on product fit and brand fit.Originality/value – The study demonstrates the focal role of positioning strategies of partner brands in consumer evaluation of cobrands. Acknowledgements : The authors thank Mr Atanas Panadaliev for his assistance during the design stage and data collection.